2020
DOI: 10.1186/s12864-020-06884-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate genes and regulatory factors related to growth rate through hypothalamus transcriptome analyses in broiler chickens

Abstract: Background: Intensive selection for growth rate (GR) in broiler chickens carries negative after-effects, such as aberrations in skeletal development and the immune system, heart failure, and deterioration of meat quality. In Poland, fast-growing chicken populations are highly non-uniform in term of growth rate, which is highly unprofitable for poultry producers. Therefore, the identification of genetic markers for boiler GR that could support the selection process is needed. The hypothalamus is strongly associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…CD36 is a candidate gene for pendulous comb [ 116 ] and related to adipogenesis and lipogenesis in pectoralis muscle tissue [ 117 ]. In the meat-type breed, signals of selective sweeps overlapped with OVST (ovostatin) [ 118 ], PMCH (promelanin concentrating hormone) [ 37 , 119 ], and SLC2A14 (solute carrier family 2 member 14) [ 120 ]. The OVST gene is involved in oviduct development and eggshell formation [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CD36 is a candidate gene for pendulous comb [ 116 ] and related to adipogenesis and lipogenesis in pectoralis muscle tissue [ 117 ]. In the meat-type breed, signals of selective sweeps overlapped with OVST (ovostatin) [ 118 ], PMCH (promelanin concentrating hormone) [ 37 , 119 ], and SLC2A14 (solute carrier family 2 member 14) [ 120 ]. The OVST gene is involved in oviduct development and eggshell formation [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…The OVST gene is involved in oviduct development and eggshell formation [ 118 ]. PMCH is a candidate gene involved in chicken growth control and overexpressed in low growth rate broiler cockerels [ 119 ] that also contributes to appetite and food intake [ 37 , 118 ]. SLC2A14 is supposedly a candidate gene for pigment synthesis [ 120 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DKK3 is known to suppress tumor growth by inhibiting cancer cell proliferation in human [ 173 , 174 , 175 ]. In another study, POMC , NMU , NPW , PMCH , GAL , and FOS were determined to be related to the broiler growth rate, as variable growth was attributed to their differential expression in the hypothalamus [ 176 ]. In a comprehensive study of DEGs that included principal component analysis, Nihashi et al [ 177 ] identified 13 candidate genes potentially related to myoblast proliferation and differentiation in chickens ( CDKN2B , ACTC1 , MYH15 , TNNI1 , TNNI2 , TNNT2 , CCK , CXCL14 , MDK , PENK , CSRP2 , MFAP5 , and UCHL1 ).…”
Section: Candidate Genes Affecting Muscle Development In Chickensmentioning
confidence: 99%
“…The hypothalamus was an important nerve center that regulates the body and endocrine activities, as well as an important center of neuroendocrine. It can regulate the secretion of hormones in the pituitary gland and the activities of its target glands, including reproduction and growth (31). Here, we initially identified 1,836 DEGs and 28 DEMs from FP-HY vs. FP-LY comparison in the hypothalamus by RNAseq.…”
Section: Discussionmentioning
confidence: 99%